Studi Evaluasi Kebijakan Kota Layak Anak (KLA) dalam Pemenuhan Klaster Hak Sipil dan Kebebasan di Kota Semarang - M. Tegar Tomi Liwananda; Lusia Astrika (Journal of Politic and Government Studies, 2020)
Child Friendly City programs run by the government would not run smoothly without thehelp of elements of the community. They must be aware that this is a joint responsibility andnot the work of just the government, so that synergy between government and the communitymust be committed and there must be a commitment from the community to implement theChild Friendly Cities program. Fulfillment of civil rights and freedoms which are the mostfundamental rights that must be owned by children and must be fulfilled by the Semarang CityGovernment in the context of Child Friendly Cities.This study aims to evaluate how the policy of the Child-Friendly Cities, especially in thefulfillment of civil rights and freedom clusters in Semarang City and what are the obstaclesencountered. The method used is a qualitative method by taking data through interviews anddocumentation. This study uses the policy evaluation theory of William Dunn which is dividedinto 6 indicators, consists of effectiveness, efficiency, adequacy, leveling, responsiveness, andaccuracy.The results of this study indicate that the fulfillment of civil rights clusters and freedom ofChild-Friendly City policies in Semarang City cannot be said to meet targets. The lack ofstrengthening of the children's forum, the stagnation of providing adequate information onchildren, as well as the achievement of the issuance of birth certificates that did not reach thetarget became the main points of evaluation. Lack of socialization to the community, lack ofcommunication between local government organizations, lack of available resources, andregulations that obstruct the implementation of the Child-Friendly City in Semarang CityGovernment.One recommendation that researchers can give to the government is to add resources andalso to issue new, stronger regulations so that they can adjust to the conditions faced in thefield.Kata kunci: Child-Friendly City, evaluation, policy